Preparation and Assessment of Some Characteristics of Nanoparticles Based on Sodium Alginate, Chitosan, and Camellia chrysantha Polyphenols - Phu Hoang Luong; Thuy Chinh Nguyen; The Dan Pham; Do Mai Trang Tran; Thi Ngoc Lien Ly; Quoc Trung Vu; Thi Kim Ngan Tran; Hoang Thai (International Journal of Polymer Science, 2021)
This paper presents the characteristics, morphology, and properties of alginate/chitosan/polyphenol nanoparticles, in which polyphenols were extracted from Camellia chrysantha leaves collected in Tam Dao district, Vinh Phuc province (Vietnam). The alginate/chitosan/polyphenol nanoparticles were prepared by ionic gelation method at different polyphenol content. The characteristics and morphology of these nanoparticles were investigated using infrared spectroscopy (IR), ultraviolet-visible spectroscopy (UV-Vis), and scanning electron microscopy (SEM). Release kinetic of polyphenols from the alginate/chitosan/polyphenol nanoparticles was conducted in simulated human body fluids. The release kinetics of polyphenols from the above nanoparticles were also evaluated and discussed. The experimental results showed that the release process of polyphenols from the nanoparticles was dependent on three factors: time, pH of solution, and amount of polyphenols.